(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Restoring soils contaminated with petroleum oil via bioremediation is both environmentally friendly and economical. A new and sustainable approach, bioremediation can either occur naturally or can be improved by adding nutrients. Five bacterial isolates were isolated, and their biodegradation ability was initially tested. The results showed that isolate FB1 was the most effective in decomposing crude oil, with a percentage of 69%. It was diagnosed at the phenotypic, chemical, and molecular levels. It was discovered to belong to the genus Bacillus spp.